2016
DOI: 10.1128/msphere.00074-16
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum-Mitochondrion Tether ERMES Orchestrates Fungal Immune Evasion, Illuminating Inflammasome Responses to Hyphal Signals

Abstract: The yeast Candida albicans causes human infections that have mortality rates approaching 50%. The key to developing improved therapeutics is to understand the host-pathogen interface. A critical interaction is that with macrophages: intracellular Candida triggers the NLRP3/caspase-1 inflammasome for escape through lytic host cell death, but this also activates antifungal responses. To better understand how the inflammasome response to Candida is fine-tuned, we established live-cell imaging of inflammasome acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 58 publications
9
42
0
1
Order By: Relevance
“…We further demonstrated that inactivation of ERMES crippled the ability of C. albicans to evade innate immunity by macrophages, and further led to loss of fitness, particularly at host temperature of 37°C and particularly after long term, chronic inactivation of ERMES function in gene deletion mutants (Tucey et al, 2016 ). Genetic and cell biology data support the existence of an ERMES complex in C. albicans that is of equivalent composition as in S. cerevisiae , with four core subunits: Mmm1, Mdm10, Mdm34, and Mdm12 (Kornmann et al, 2009 ; Tucey et al, 2016 ). ERMES is conserved within fungi (Wideman et al, 2013 ), and a recent study of ERMES in the pathogenic mold Aspergillus fumigatus supports the idea that targeting ER-Mitochondria interactions might be promising as a therapeutic strategy against multiple, divergent pathogenic fungal species (Geißel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…We further demonstrated that inactivation of ERMES crippled the ability of C. albicans to evade innate immunity by macrophages, and further led to loss of fitness, particularly at host temperature of 37°C and particularly after long term, chronic inactivation of ERMES function in gene deletion mutants (Tucey et al, 2016 ). Genetic and cell biology data support the existence of an ERMES complex in C. albicans that is of equivalent composition as in S. cerevisiae , with four core subunits: Mmm1, Mdm10, Mdm34, and Mdm12 (Kornmann et al, 2009 ; Tucey et al, 2016 ). ERMES is conserved within fungi (Wideman et al, 2013 ), and a recent study of ERMES in the pathogenic mold Aspergillus fumigatus supports the idea that targeting ER-Mitochondria interactions might be promising as a therapeutic strategy against multiple, divergent pathogenic fungal species (Geißel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 87%
“…They are also significant because during evolution ERMES has been lost in metazoans, and therefore no human homologs exist (Wideman et al, 2013 ), and in the human pathogenic yeast Candida albicans repression of MMM1 , the gene encoding the ER-anchored subunit of the ERMES, blocks virulence in mice infection (Becker et al, 2010 ). We recently performed the first detailed characterization of the ERMES complex in a human fungal pathogen, showing that the principal role of ERMES in C. albicans is to enable proper mitochondrial morphology (Tucey et al, 2016 ). We further demonstrated that inactivation of ERMES crippled the ability of C. albicans to evade innate immunity by macrophages, and further led to loss of fitness, particularly at host temperature of 37°C and particularly after long term, chronic inactivation of ERMES function in gene deletion mutants (Tucey et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tucey et al (2016) characterized the C. albicans endoplasmic reticulum (ER)-mitochondria tether complex ERMES (mediator of interactions between organelles, providing membrane contact sites) and showed that the ERMES mmm1 mutant has a severely crippled ability to kill macrophages despite hyphal formation and normal phagocytosis and survival.…”
Section: Controlmentioning
confidence: 99%
“…Fission has been shown to isolate defective parts of the network and facilitate their turnover by mitophagy (Mao and Klionsky 2013). In recent years, much of the machinery governing fission and fusion has been elucidated (Pagliuso, Cossart and Stavru 2018), including important contributors such as interaction with the ER (Tucey et al 2016). As mitochondrial function is implicated in a wide variety of pathologies and stress responses, the study of mitochondrial morphology in pathogens such as C. albicans could be used to better understand the host-pathogen interaction.…”
Section: Introductionmentioning
confidence: 99%